Effects of LED spectral compositions on yield, growth, and nutritional quality of basil microgreens in indoor vertical farming - Sibel Balik; Abdullah Aldiyab; Tuğçe Temtek; Boran İkiz; Hayriye Yildiz Dasgan; Nazim S. Gruda (PLoS ONE, 2026)
Light quality, particularly the spectral composition emitted by LEDs, modulate growth dynamics, physiological processes, and the nutritional attributes of microgreens cultivated under controlled environments. In this study, the effects of three distinct LED spectra on growth performance, pigmentation, and nutritional composition of basil ( Ocimum basilicum L.) microgreens were assessed within an indoor vertical farming system. The lighting treatments included: (LED1) 70% red (660 nm) + 30% blue (450 nm), (LED 2) a full-spectrum PAR range (400–700 nm), and (LED 3) 65% red (660 nm), 25% blue (450 nm), 5% white (broad spectrum around 400–700 nm), and 5% far-red (730 nm). Key parameters assessed were plant height, hypocotyl length, stem diameter, individual plant fresh weight, yield, color values (L* = luminosity, a* = red-green axis, b* = blue-yellow axis), dry matter content, macro and micronutrient levels, pH (hydrogen ion concentration) and titratable acidity (total acidity), soluble solid content (SSC), electrical conductivity (EC), and concentrations of oil, total phenols, flavonoids, and vitamin C. Among the treatments, LED 3 significantly enhanced plant height, hypocotyl length, yield, total phenol content, acidity, EC, and color brightness (L*), highlighting its superior overall performance. LED 2 was most effective in increasing vitamin C, flavonoid, and oil content, while LED 1 promoted higher dry matter and mineral contents. These findings emphasize the importance of optimizing LED spectra to improve both productivity and nutritional quality. Based on its consistent advantages across multiple parameters, LED 3 is the most advantageous in terms of yield, biomass accumulation, and visual quality, highlighting its potential suitability for commercial microgreen cultivation in controlled environment systems. Further research is needed to validate these findings across different cultivar-specific responses and environmental conditions.